2005
DOI: 10.2152/jmi.52.33
|View full text |Cite
|
Sign up to set email alerts
|

Overweight is associated with allergy in school children of Taiwan and Vietnam but not Japan

Abstract: We collected information concerning diagnosed allergy from 2027 school children in Japan, Taiwan and Vietnam. Children were classified according to the age and sex-specific body mass index (BMI) per-age as indicator of weight status. Logistic regression was performed to examine the relationship between percentiles of BMI-per-age and allergy. Compared with children at the lowest percentile group Taiwanese children at > 85th percentile group showed a tendency toward higher risk of allergy (OR = 1.79, 95% CI 0.98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, others have not confirmed this association [25-27]. Furthermore, among studies finding a significant association, food allergy has been pinpointed as the driving force of the association in some studies [2,28] and rhino-conjunctivitis in another [25]. …”
Section: Discussionmentioning
confidence: 99%
“…However, others have not confirmed this association [25-27]. Furthermore, among studies finding a significant association, food allergy has been pinpointed as the driving force of the association in some studies [2,28] and rhino-conjunctivitis in another [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The results of investigations of the association between BMI and eczema and rhinoconjunctivitis have been conflicting (13)(14)(15)(16)(17). Among Belgian schoolchildren, there was no association between BMI and the prevalence of eczema or rhinoconjunctivitis (13).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in adults have shown that obesity and overweight are positively associated with asthma or asthma-like symptoms (1)(2)(3)(4)(5)(6)(7)(8)(9); moreover, in some studies, this association was more pronounced in women than in men (1,(7)(8)(9). In children, on the other hand, results concerning the association of asthma with obesity have not been consistent (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Data from the National Health and Nutrition Examination Survey showed that a higher body mass index (BMI) was associated with an increased prevalence of asthma among 7505 US children aged 4-17 years (10).…”
Section: Introductionmentioning
confidence: 95%
“…After review of the titles and abstracts, 536 articles did not meet our inclusion criteria, and 12 were excluded 31-42 for a lack of data for the frequency of AD/eczema or BMI classification. In total, 30 studies 26,33, were included in the review, of which 20 had valid data that could be pooled to assess for the effects of overweight, 26,43,47,50,[53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] 23 for obesity, 26,33,43,45,47,50,[52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] and 26 for overweight/obesity. 26,43,44,[46]…”
Section: Literature Searchmentioning
confidence: 99%